2017
DOI: 10.1089/brain.2016.0468
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Network Analysis of Whole-Brain Resting-State Functional Connectivity in Spinal Cord Injury: A Comparative Study

Abstract: Network analysis based on graph theory depicts the brain as a complex network that allows inspection of overall brain connectivity pattern and calculation of quantifiable network metrics. To date, large-scale network analysis has not been applied to resting-state functional networks in complete spinal cord injury (SCI) patients. To characterize modular reorganization of whole brain into constituent nodes and compare network metrics between SCI and control subjects, fifteen subjects with chronic complete cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 79 publications
0
19
1
1
Order By: Relevance
“…They moreover observed enhanced connectivity strengths in a sub-network containing midline sensorimotor cortex and left CB of SCI patients, attributing it to a higher degree of neuronal intercommunication of those areas due to the injury. Kaushal et al ( 2017b ) also applied large-scale GA to their data to further analyze the RS networks of the SCI patients in comparison to those of healthy individuals. They calculated correlation between pairs the already defined ROIs and then calculated modularity, as well as local and global efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…They moreover observed enhanced connectivity strengths in a sub-network containing midline sensorimotor cortex and left CB of SCI patients, attributing it to a higher degree of neuronal intercommunication of those areas due to the injury. Kaushal et al ( 2017b ) also applied large-scale GA to their data to further analyze the RS networks of the SCI patients in comparison to those of healthy individuals. They calculated correlation between pairs the already defined ROIs and then calculated modularity, as well as local and global efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research using resting-state fMRI has reported a decrease in functional connectivity (FC) between cortical sensorimotor regions after SCI. 9-15 Such alterations in resting-state properties have been shown by a previous study to hold significant implications for the prognosis of SCI at 6 months postinjury. 15 Findings from alternative approaches such as graph analysis provide evidence for preserved small-worldness with reduced local efficiency and greater network modularity and characteristic path length in the network architecture of SCI patients.…”
Section: Introductionmentioning
confidence: 69%
“…15 Findings from alternative approaches such as graph analysis provide evidence for preserved small-worldness with reduced local efficiency and greater network modularity and characteristic path length in the network architecture of SCI patients. 10,16 However, the translation of cortical reorganization into clinical biomarkers is yet to be established. This gap in our knowledge of neuroplasticity and functional recovery may pertain to the subcortical substrates of SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Functional connectivity (FC) after SCI has been studied by means of electroencephalography (EEG) [ 9 15 ] and functional magnetic resonance imaging (fMRI) [ 6 , 16 21 ]. Poor recovery after SCI has been associated with decreased FC strengths between midline sensorimotor network nodes during resting state, while the opposite pattern has been associated with good recovery [ 6 ].…”
Section: Introductionmentioning
confidence: 99%